RANCANG BANGUN SISTEM KECEPATAN ANGIN BERBASIS MIKROKONTROLER - Didi, Didi Sahrudin Buton; Santosa, Santosa; Dzikrullah, Muh (PRODUKTIF : Jurnal Ilmiah Pendidikan Teknologi Informasi, 2023)
The purpose of this research is to design and build a wind speed monitoring system using anemometer sensor, Arduino Uno and LCD16x2 as data display and Via Buzeer as an alarm when the wind speed is high. Design and build a wind speed monitoring system using an anemometer sensor and Arduino uno. In this study will provide more benefits to users in everyday life. Experimental research is unique in two very important respects. This research is the only type of research that directly tries to influence a particular variable, and when properly applied. This research is also a good type of research in testing hypotheses, causality, or quality (Fraenkel et al). the results of this study all the tools or devices for wind speed monitoring systems, namely Arduino Uno, Anemometer Sensors and several other components can function properly. Test results using Arduino Uno and LCD16x2, Via Buzzer can run well. From experiments carried out using the Anemometer Sensor, once the propeller is rotated, wind speed data can be sent to the Lcd16x, and when the wind tension is very high, the notification enters via the Via Buzeer as an alarm means that the wind speed is very high. all devices can function properly and run as expected.